Semi-regular Quadrilateral-only Remeshing from Simplified Base Domains - Daniels II, Joel; Silva, Claudio T.; Cohen, Elaine (Computer graphics forum, 2009)
Semi‐regular meshes describe surface models that exhibit a structural regularity that facilitates many geometric processing algorithms. We introduce a technique to construct semi‐regular, quad‐only meshes from input surface meshes of arbitrary polygonal type and genus. The algorithm generates a quad‐only model through subdivision of the input polygons, then simplifies to a base domain that is homeomorphic to the original mesh. During the simplification, a novel hierarchical mapping method, keyframe mapping, stores specific levels‐of‐detail to guide the mapping of the original vertices to the base domain. The algorithm implements a scheme for refinement with adaptive resampling of the base domain and backward projects to the original surface. As a byproduct of the remeshing scheme, a surface parameterization is associated with the remesh vertices to facilitate subsequent geometric processing, i.e. texture mapping, subdivision surfaces and spline‐based modeling.